(untitled) (Terr@ Plural, 2021)
Despite being known since the 19th century, systematic studies of Bivalvia still face major challenges due to preservation problems of diagnostic characters and the number of specimens per taxon. Some species are well known and abundant while most are represented by few specimens or even just by their holotype. Thus, many remain considered invalid according to the International Zoological Nomenclature Code. Here we discuss the taxonomic problems about the Devonian Bivalvia group in Brazil, emphasizing biodiversity, stratigraphic positioning, and geographic distribution in four intracratonic sedimentary basins - Amazonas, Paraná, Parnaíba, and Jatobá. Seventy-seven taxa were identified - 66 distributed in 2 subclasses, 3 infraclasses, 18 families, and 30 genera, plus 11 species in supraspecific taxonomic discussion. Of the bivalves studied, 10 still do not have a specific epithet, demonstrating the need for more accurate studies for the taxon. The greatest diversity is found in the Amazon Basin, with 39 species, followed by the Paraná Basin (24 species); the Parnaíba Basin (11 species), and the Jatobá Basin (8 species). There are shares of taxa between at least two to three basins, as well as the diversity of a certain genus for a given basin. This can be evidenced mainly by the genera: Palaeoneilo and Grammysioidea occurring among the Amazon, Parnaíba and Paraná basins; Cypricardella and Sanguinolites in the Amazon, Paraná and Jatobá basins; Nuculites (Nuculites) in the Parnaíba, Paraná and Jatobá basins; and Spathella in the Amazonas, Parnaíba and Jatobá basins. The greater genera sharing was noted between the Amazon and Paraná basins (7 genera), followed by the Amazon and Parnaíba basins (5 genera), the Amazon and Jatobá basins (4 genera), Parnaíba basins and Paraná (3 genera), and Parnaíba and Jatobá basins (2 genera). This may have been due to the greater diversity of bivalves in the Amazon Basin, as well as the events of marine warm and extensive marine transgressions of the Middle and Upper Devonian recorded. Regarding species, Spathella pimentana, Grammysioidea lundi, Sanguinolites(?) karsteni, and Cucullella triquetra are found both in outcrops of the Amazonas Basin and in the Parnaíba Basin, while Nuculites aff N. oblongatus is in the Parnaíba and Jatobá basins, wich reveals a close connection among these basins during the Devonian.